Eco-friendly Pest Control using Organic Materials: Cinnamomum Verum, Garlic and Chili - Adnan, Nurul Izzah Adnan; Pauzan, Dr. Mohammad Arif Budiman; Ruslan, Nurun Najwa (Journal of Science and Technology, 2025)
The widespread use of chemical pesticides in agriculture poses environmental risks and health concerns prompting the development of green alternatives from natural sources. This study aims to synthesize a natural pesticide using a mixture of Cinnamomum Verum (cinnamon) essential oil, garlic and chili and characterize the functional group of the formulation. The pesticide was prepared by extracting Cinnamomum Verum essential oil through distillation and creating garlic and chili solutions by grinding the ingredients with distilled water. The formulation consisted of 25% Cinnamomum Verum essential oil (50 mL) mixed with 75% garlic and chili solution (150 mL) in a 1:3 ratio. Active components including eugenol from Cinnamomum Verum, capsaicin from chili and allicin from garlic were identified through FTIR analysis confirming potential as natural repellents. The formulated pesticide demonstrates promising pest-repellent properties by effectively reducing pest infestation and leaf damage on chili plants during field evaluations. The synergistic combination of these plant-based bioactive compounds offers a potent, eco-friendly solution for pest control thus contribute to sustainable agricultural practices and safeguarding ecological health.